Food Security and Diversity of Coastal Communities in West Papua Province, Indonesia - Fitryanti Pakiding (Fakultas Teknologi Pertanian, Universitas Papua, Manokwari, 2022)
Food security is a condition of fulfilling food at the country scale down to individuals, which is reflected in the availability of sufficient food, both in quantity and quality, safe, diverse, nutritious, equitable, and affordable. It does not conflict with the religion, beliefs, and culture of society to be able to live a healthy life, active and productive in a sustainable manner. One of the crucial groups of people who live in West Papua Province is the coastal communities of West Papua. This study aims to provide information on the status of food security and the diversity of families living in the coastal areas of West Papua Province. In particular, we conducted this research to obtain information on food security and diversity status in terms of food access and utilization pillars. Measuring household food security status using the U.S. Household Food Security Survey Module (US HFSSM) and measuring diversity in food consumption based on the household dietary diversity score (HDDS). The results showed that household food security in the coastal area of ​​the bird's head was quite good; Cendrawasih Bay National Park was the most food-secure area at 77.16%, and the least food secure was the Sorong coast at 29.76%. The highest food diversity was in the Misool area, 77.47%, and the lowest was in Telma, 22.08%.